KONSEP AL-NAFS DALAM AL-QUR´AN MENURUT KITAB IBNU KATSIR - dan Aisyah Arsyad, Murni Tamulis (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2024)
This study aims to conduct an in-depth analysis of the concept of Al-Nafs in the understanding and Book of Tafsir written by Ibn Kathir. The concept of Nafs itself is one of the important parts in the aspect of human life as a whole being that has spiritual and physical elements. This study was conducted using the library research method with the content analysis technique where the author conducted a study of the book of tafsir written by Ibn Kathir which discusses the concept of Al-Nafs. In Ibn Kathir's interpretation, there are several verses in the Qur'an that discuss in detail about Al-Nafs. Ibn Kathir's opinion about Nafs is based on a literal interpretation (Text) where the word nafs is interpreted as the process of human creation starting from Adam and Eve as explained in QS. Al-Mu'minun / 23: 12-16. In addition, in QS Yusuf / 12: 53, Al-Nafs is interpreted as part of lust both in terms of anger (negative) and love (positive) towards fellow human beings. Then in QS Al -Qiyamah/75:2 Ibn Kathir interprets that humans need to purify their souls from regrettable mistakes before facing the afterlife, this is connected to the command of Allah SWT to always repent. Furthermore, QS Al-Isra verses 31 and 33 and QS Al-Ma'idah: Verse 32 which explain the existence of a strict prohibition not to kill each other without a fundamental thing to protect the nature of humans as the noble creation of Allah SWT.